How Does Trade Openness Influence Budget Deficits in Developing Countries? - Combes, Jean-Louis.; Saadi-Sedik, Tahsin (Washington, D.C. : International Monetary Fund, 2006)
This paper analyzes the effects of trade openness on budget balances by distinguishing the effects of natural openness from those of trade-policy induced openness. Using the GMMsystem estimator, the econometric analysis focuses on 66 developing countries during 1974-98. The results show that trade openness increases a country's exposure to external shocks regardless of its underlying causes. This reinforces the adverse effects of terms of trade instability on budget balances. However, trade openness also influences budget balances through several other channels: corruption, income inequalities, et cetera The paper shows that these additional effects of natural openness and trade-policy induced openness on budget balances go in opposite directions: the former deteriorates budget balances whereas the latter improves them.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet